Approaching a half-century of dancing - Philip Cu-Unjieng (2019)
Now on its 49th season at the Cultural Center of the Philippines (CCP), resident dance company Ballet Philippines just completed its penultimate offering of the season, the romantic Romeo & Juliet.
And for those who got to catch this wonderfully staged classical piece, it was a vivid reminder of how ballet is a theatrical spectacle, a showcase of physical skills and can be as relevant today as it's ever been.
With National Artist for Dance Alice Reyes back at the helm as artistic director, a position she occupied when the company was founded in 1969, there is a special element of coming full circle. And there will definitely be something poetic about this later in the year, as the company ushers in its 50th year. Visit College of Music Library for Full Article.
Keywords: Ballet Philippines